Transcranial Sonography in the Diagnosis of Pituitary Tumor—A Direct Comparison With MRI - He, Lei; Zhang, Jinghan; Yu, Tengfei; Du, Yue; Liu, Xinyao; He, Wen (Frontiers in Endocrinology, 2021)
Background: Transcranial sonography (TCS) is a convenient tool for detecting certain brain diseases, such as brain tumor. Seldom study had reported the use of TCS in the area of Sella turcica. TCS’ accuracy and repeatability of Sella turcica with or without pituitary tumor is not clear. Purpose: To investigate the feasibility and accuracy of TCS to measure the size of Sella turcica according to the measurement in MRI and determine its diagnostic performance in individuals with pituitary tumor. Materials and Methods: In this cross-sectional comparative study, health volunteers and patients with pituitary tumor were enrolled to perform examination of TCS and MRI between Oct 2020 and Jul 2021. The transverse diameter (D1) of Sella turcica and volume of pituitary tumor were measured by TCS and MRI separately and compared by using Student’s t test or Mann–Whitney test. Using ROC curve to analyze the diagnostic value of D1 in TCS for pituitary tumor. Results: A total of 75 health volunteers and 51 patients with pituitary tumor were evaluated. In health volunteer, the mean D1 was 1.30±0.35 ( rang, 0.82-3.22) by TCS and 1.32±0.29（rang,0.94-3.02）by MRI (P=0.054). In patients with pituitary tumor, the mean D1 was 2.0±0.65 (rang,0.90-3.48) by TCS and 2.42±1.0 (rang, 0.80-4.70) by MRI (P=0.000). The median measurement volume was 4.41 and 6.59 cm3 in TCS and MR separately(P=0.000). The mean D1 was 1.31±0.35 in health volunteer and 2.0±0.65 in patients with pituitary tumor (P=0.000). In the ROC curve analysis, the AUC was 0.836, and the optimal cutoff value (1.56) exhibited a sensitivity and specificity of 67.31% and 88.0%, respectively. Conclusion: The consistency between two imaging technology is well in D1 measurement, while pituitary tumor’s volume is smaller assessed by TCS than MRI. D1 in TCS has good diagnostic performance in pituitary tumor.